Tolerance Optimization for Composite Structures - Franz, Michael; Freitag, Stephan; Wartzack, Sandro (Research in Tolerancing, 2024)
With rising demands and regulations for efficient and sustainable products, the use of high performance composite materials rises. There are a large number of manufacturing processes for composite materials, which inevitably lead to variations. Consideration of variations during product development is therefore particularly important for products of larger quantities. For this reason, this publication analyzes the variations and then applies methods from tolerance management to take them into account. Therefore, an approach for tolerance analysis and optimization is presented, with which the tolerance ranges of varying laminate parameters are analyzed and optimized. With this approach, not only one design parameter can be optimized, but it enables the simultaneous optimization of different parameter types like ply angle or ply thickness. Furthermore, surrogate models are used to reduce the computational effor